2015
DOI: 10.1016/j.chemphys.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of TiO2:Ag nanocrystalline heterostructures: Experimental and theoretical insights

Abstract: We report the synthesis and characterization of silver-decorated titanium dioxide (TiO 2 :Ag) nanoparticles, as well as a discussion of their antimicrobial activity. This material was synthesized by microwave-assisted hydrothermal treatment and characterized by complementary techniques. The minimum inhibitory concentration and minimum bactericidal/fungicidal concentration of TiO 2 :Ag nanoparticles against planktonic and biofilm-forming strains of methicillin-resistant Staphylococcus aureus, Candida species (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Furthermore, Figure 6 shows that Ag-TiO 2 thin films showed an important increase in the photocatalytic activity under UV (near 35%); these results could be due to the silver aggregates deposited on the TiO 2 surface that can accumulate charge and accept electrons inside the semiconductor. The accumulation of electrons can reduce the carrier's recombination increasing generation of reactive oxygen species, and besides, Ag particle on TiO 2 can change and a collective oscillation can be generated, which is known as localized surface plasmon resonance (SPR) [49]; according to other reports, silver particles exhibit collective oscillation of their electrons in the conduction band, and it is suggested that the association between the semiconductor and the metal can increase photocatalytic activity, which coincides with the results obtained in this work [50]. Pseudo-first-order model was applied to kinetic data of Figure 6.…”
supporting
confidence: 89%
“…Furthermore, Figure 6 shows that Ag-TiO 2 thin films showed an important increase in the photocatalytic activity under UV (near 35%); these results could be due to the silver aggregates deposited on the TiO 2 surface that can accumulate charge and accept electrons inside the semiconductor. The accumulation of electrons can reduce the carrier's recombination increasing generation of reactive oxygen species, and besides, Ag particle on TiO 2 can change and a collective oscillation can be generated, which is known as localized surface plasmon resonance (SPR) [49]; according to other reports, silver particles exhibit collective oscillation of their electrons in the conduction band, and it is suggested that the association between the semiconductor and the metal can increase photocatalytic activity, which coincides with the results obtained in this work [50]. Pseudo-first-order model was applied to kinetic data of Figure 6.…”
supporting
confidence: 89%
“…MICs were recorded as the lowest concentrations of each solution to achieve complete inhibition of growth (without visible growth by visual inspection). 43,44 MFCs/MBCs were determined by inoculating 25 μL aliquots, taken from 10-fold serial dilutions (10 −1 to 10 −8 ) of each well, on plates containing SDA for C. albicans and Mueller−Hinton agar for MRSA and E. coli, in duplicate. After the cells were incubated at 37 °C for 24−48 h, the CFU/mL was calculated and log 10 -transformed.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of this, the metal may inject electrons into the semiconductor, creating points defects with partially located electrons and holes on its surface. This involves the formation of superoxides, hydrogen ions (H+), and/or OOH* radicals, a consequence of electron-hole reactions, causing protein inactivation and cellular death (apoptosis) [ 67 , 68 ]. Consequently, it can be said that this association can be extremely effective in preventing biofilm formation and decreasing the number of bacteria [ 69 ].…”
Section: Resultsmentioning
confidence: 99%